Interferência de Pratylenchus Brachyurus em soja sob diferentes sistemas de cultivo e desempenho agronômico de cultivares de batata-doce em área infestada com Meloidogyne Incognita - Lima, Fábia Silva de Oliveira (Universidade Federal do Tocantins, 2017)
Pratylenchus brachyurus has become increasingly frequent in soybean fields throughout Brazil where yield loss assessments have reported reduction up to 30%. Currently, no soybean cultivars resistant to P. brachyurus have been identified and management strategies include crop rotation with non-host crops, fallow, and the application of nematicides. The goals of this study were to examine the population dynamics of P. brachyurus in soybean fields throughout Tocantins state and in areas planted with off-season crops following soybean harvest in a crop succession scheme. Pratylenchus brachyurus was present in ca. 82% of samples with densities in soybean fields ranging from 23 to 20,400 nematodes per 200 cm3 soil or 10g root samples. In two sites, the mean nematode density was higher within infestation foci which were characterized by poor soybean growth compared to those from outside infestation foci, with an overall reduction of 44.3% in plant height and 39.7% in pod numbers. Following soybean harvest in areas planted with off-season crops including maize, sorghum, millet, crotalaria as well as an area maintained as a fallow treatment, the mean density of P. brachyurus ranged from 122 to 504 individuals per 10 g root sample and from 3 to 96 per 200 cm3 soil. Overall, the mean density of nematodes did not differ significantly among plant species and all crops used in the succession scheme allowed P. brachyurus multiplication. In summary, off-season cultivation with the crops used in this study is not recommended for management of P. brachyurus in soybean, but the use of fallow or non-hosts may be helpful in lowering the population density of P. brachyurus in soybean fields.